OsG6PGH1 affects various grain quality traits and participates in the salt stress response of rice - Peng, Bo; Liu, Yan; Qiu, Jing; Peng, Jing; Sun, Xiaoyu; Tian, Xiayu; Zhang, Zhiguo; Huang, Yaqin; Pang, Ruihua; Zhou, Wei; Zhao, Jinhui; Sun, Yanfang; et al. (Frontiers in Plant Science, 2024)
Cytoplasmic 6-phosphogluconate dehydrogenase (G6PGH) is a key enzyme in the pentose phosphate pathway that is involved in regulating various biological processes such as material metabolism, and growth and development in plants. However, it was unclear if OsG6PGH1 affected rice grain quality traits. We perform yeast one-hybrid experiments and reveal that OsG6PGH1 may interact with OsAAP6.Subsequently, yeast in vivo point-to-point experiments and local surface plasmon resonance experiments verified that OsG6PGH1 can bind to OsAAP6. OsG6PGH1 in rice is a constitutive expressed gene that may be localized in the cytoplasm. OsAAP6 and protein-synthesis metabolism-related genes are significantly upregulated in OsG6PGH1 overexpressing transgenic positive endosperm, corresponding to a significant increase in the number of protein bodies II, promoting accumulation of related storage proteins, a significant increase in grain protein content (GPC), and improved rice nutritional quality. OsG6PGH1 positively regulates amylose content, negatively regulates chalkiness rate and taste value, significantly affects grain quality traits such as appearance, cooking, and eating qualities of rice, and is involved in regulating the expression of salt stress related genes, thereby enhancing the salt-stress tolerance of rice. Therefore, OsG6PGH1 represents an important genetic resource to assist in the design of high-quality and multi-resistant rice varieties.